The durable differential deterrent effects of strict photo identification laws. Issue 3 (28th July 2022) - Grimmer, Justin; Yoder, Jesse
Abstract: An increasing number of states have adopted laws that require voters to show photo identification to vote. We show that the differential effect of the laws on turnout among those who lack ID persists even after the laws are repealed. We leverage administrative data from North Carolina and a photo ID law in effect for a primary, but not the subsequent general, election. Using exact matching and a difference-in-differences design, we show that for the 3 percent of voters who lack ID in North Carolina, the ID law caused a 0.7 percentage point turnout decrease in the 2016 primary election relative to those with ID. After the law was suspended, this effect persisted: those without ID were 2.6 percentage points less likely to turnout in the 2016 general election and 1.7 percentage points less likely to turnout in the 2018 general.